Genomic profiling reveals distinctive molecular relapse patterns in IDH1/2 wild-type glioblastoma. - Riehmer, V.; Gietzelt, J.; Beyer, U.; Hentschel, B.; Westphal, M.; Schackert, G.; Sabel, M. C.; Radlwimmer, B.; Pietsch, T.; Reifenberger, G.; Weller, M.; Weber, R. G.; et al. (Genes Chromosomes Cancer, 2014)
Molecular changes associated with the progression of glioblastoma after standard radiochemotherapy remain poorly understood. We compared genomic profiles of 27 paired primary and recurrent IDH1/2 wild-type glioblastomas by genome-wide array-based comparative genomic hybridization. By bioinformatic analysis, primary and recurrent tumor profiles were normalized and segmented, chromosomal gains and losses identified taking the tumor cell content into account, and difference profiles deduced. Seven of 27 (26%) pairs lacked DNA copy number differences between primary and recurrent tumors (equal pairs). The recurrent tumors in 9/27 (33%) pairs contained all chromosomal imbalances of the primary tumors plus additional ones, suggesting a sequential acquisition of and/or selection for aberrations during progression (sequential pairs). In 11/27 (41%) pairs, the profiles of primary and recurrent tumors were divergent, i.e., the recurrent tumors contained additional aberrations but had lost others, suggesting a polyclonal composition of the primary tumors and considerable clonal evolution (discrepant pairs). Losses on 9p21.3 harboring the CDKN2A/B locus were significantly more common in primary tumors from sequential and discrepant (nonequal) pairs. Nonequal pairs showed ten regions of recurrent genomic differences between primary and recurrent tumors harboring 46 candidate genes associated with tumor recurrence. In particular, copy numbers of genes encoding apoptosis regulators were frequently changed at progression. In summary, approximately 25% of IDH1/2 wild-type glioblastoma pairs have stable genomic imbalances. In contrast, approximately 75% of IDH1/2 wild-type glioblastomas undergo further genomic aberrations and alter their clonal composition upon recurrence impacting their genomic profile, a process possibly facilitated by 9p21.3 loss in the primary tumor. (c) 2014 Wiley Periodicals, Inc.
Keywords: Aged; Aged, 80 and over; Brain Neoplasms/*genetics/metabolism; DNA Copy Number Variations; Female; Glioblastoma/*genetics/metabolism; Humans; Isocitrate Dehydrogenase/*genetics; Male; Middle Aged; Neoplasm Recurrence, Local/*genetics/metabolism; Prospective Studies; Transcriptome/*physiology